2017
DOI: 10.1186/s12870-017-1165-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the auxin/indoleacetic acid (Aux/IAA) gene family in allotetraploid rapeseed (Brassica napus L.)

Abstract: Background Auxin/Indoleacetic acid (Aux/IAA) genes participate in the auxin signaling pathway and play key roles in plant growth and development. Although the Aux/IAA gene family has been identified in many plants, within allotetraploid Brassica napus little is known.ResultsIn this study, a total of 119 Aux/IAA genes were found in the genome of B. napus. They were distributed non-randomly across all 19 chromosomes and other non-anchored random scaffolds, with a symmetric distribution in the A and C subgenomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 61 publications
4
42
0
Order By: Relevance
“…Within this tree, a total of 25 sister pairs were found, consisting of 10 and 15 pairs in group A and B. This pattern of two major groups for Aux/IAA gene family members in the phylogenetic tree was similar to that reported for other plants including rice [22], Moso bamboo (Phyllostachys pubescens) [23], soybean [12] and Brassica napus [2], which suggested that the Aux/IAA genes have been widely conserved in different groups. Meanwhile, to gain a better understanding of the structural diversity of the BsIAAs, we also built a separate phylogenetic tree using the same method (Figure 4).…”
Section: Comparative Phylogenetic Analysis Of Bsiaasupporting
confidence: 81%
“…Within this tree, a total of 25 sister pairs were found, consisting of 10 and 15 pairs in group A and B. This pattern of two major groups for Aux/IAA gene family members in the phylogenetic tree was similar to that reported for other plants including rice [22], Moso bamboo (Phyllostachys pubescens) [23], soybean [12] and Brassica napus [2], which suggested that the Aux/IAA genes have been widely conserved in different groups. Meanwhile, to gain a better understanding of the structural diversity of the BsIAAs, we also built a separate phylogenetic tree using the same method (Figure 4).…”
Section: Comparative Phylogenetic Analysis Of Bsiaasupporting
confidence: 81%
“…Of these, two neighboring genes, BnaA03g36940D and BnaA03g36950D , were found to encode Aux/IAA proteins homologous to IAA2 (At3g23030) and IAA7 (At3g23050) in Arabidopsis thaliana , respectively (Fig. e) that had been established previously (Li et al ., ). In Arabidopsis , the Aux/IAA proteins act as repressors in the auxin signaling pathway and mutations of Aux/IAA genes usually generate auxin‐related growth defects, including aberrant leaf architecture and dwarfism (Reed, ; Overvoorde et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…However, most of the duplicated ANN genes were retained after the whole-genome duplication (WGD) event in B. napus. WGD event of gene family appears to be a widespread phenomenon, such as the auxin response factor (ARF) 47 , Auxin/Indoleacetic acid (Aux/IAA) 48 , glutathione transferases (GST) 49 , BRI1-EMS-SUPPRESSOR1 (BES1) 50 , Heat stress transcription factors (Hsfs) 51,52 , GRAS 53 family genes in diploid and allopolyploid Brassicaceae and Calcium-dependent protein kinases (CPK) 54 , Jasmonate ZIM-domain (JAZ) 55 and Nuclear factor YB (NF-YB) 56 in diploid and allopolyploid Gossypium species (G. raimondii: DD genome; G. arboretum: AA genome; G. hirsutum: AADD genome). Among the 51 Brassica ANN genes, 35 were the typical ANN, which encoded proteins ranging from 315-325 amino acids (AA) and contained four annexin repeats.…”
Section: Resultsmentioning
confidence: 99%